Acute hemolytic transfusion reaction due to a warm reactive anti‐A1. Issue 5 (26th February 2018) - Helmich, Floris; Baas, Inge; Ligthart, Peter; Bosch, Milou; Jonkers, Femke; de Haas, Masja; van der Graaf, Fedde
Abstract : BACKGROUND: Anti‐A1 are regularly observed by reverse testing and are generally considered clinically irrelevant. For compatibility testing and the selection of blood, we use the type‐and‐screen (T&S) strategy, in which ABO confirmation of patients with a definitive blood group is performed by forward grouping only. Because anti‐A1 seem clinically irrelevant, it is our policy to provide group A blood in patients with an anti‐A1 . STUDY DESIGN AND METHODS: This is a case report of a 96‐year‐old woman who died shortly after transfusion of blood group A red blood cells (RBCs). She was known to have blood group A2 with an anti‐A1 and the absence of other RBC antibodies. Directly after starting transfusion, acute dyspnea was observed, while other clinical signs for a transfusion reaction were absent. In the laboratory, indications for a severe hemolytic transfusion reaction (HTR) triggered serologic investigations and complement deposition experiments. RESULTS: Analyses revealed that the anti‐A1 was present as a high‐titer IgM class immunoglobulin that induced complement deposition on A1 RBCs. The anti‐A1 reacted in a wide temperature amplitude up to 37°C with A1 RBCs, while weak agglutination was observed with A2 RBCs at room temperature. CONCLUSION: A pretransfusion detectable anti‐A1 caused a severe HTR that, in view of the rapid onset of clinical symptoms and concomitant deterioration, contributed to the death of the patient. Considering its clinical significance in this case, we encourage an unambiguous procedure for patients with an anti‐A1, especially when T&S is used for donor RBC selection.